Modified Deep Anterior Lamellar Keratoplasty Technique to Rescue Failed Penetrating Keratoplasty - Lisa C; Machado Soares R; Fernández-Vega-Cueto L; Alfonso-Bartolozzi B; Alfonso JF (Clinical Ophthalmology, 2022)
Carlos Lisa,1,* Ricardo Machado Soares,2,* Luis Fernández-Vega-Cueto,1 Belén Alfonso-Bartolozzi,1 Jose F Alfonso1 1Cornea and Lens Department, Fernández-Vega Ophthalmological Institute, Oviedo, Spain; 2Department of Ophthalmology, Centro Hospitalar de Vila Nova de Gaia e Espinho, Porto, Portugal*These authors contributed equally to this workCorrespondence: Ricardo Machado Soares, department of Ophthalmology, Centro Hospitalar de Vila Nova de Gaia e Espinho, Rua Conceição Fernandes, S/N, Vila Nova de Gaia, Porto, 4434-502, Portugal, Tel +35 1915045174, Email Ricardo.machado.soares@chvng.min-saude.ptPurpose: To describe a modified deep anterior lamellar keratoplasty (DALK) technique to rescue failed penetrating keratoplasty (PK) grafts and report its results.Patients and Methods: Retrospective, case-series analysis of patients who underwent modified DALK to rescue failed corneal grafts after PK was included. Every patient had corneal graft failure (GF) diagnosis due to anterior corneal (epithelium, Bowman’s, and stroma layers) or refraction disorders uncorrectable with conservative management. The main objective of the surgery and primary outcome of the study was the improvement of corrected distance visual acuity (CDVA). The study’s secondary outcome was the frequency of intra- and postoperative complications.Results: This series included four eyes from three patients with a mean age of 57.7 years (range: 51– 63 years). Mean follow-up of patients was thirteen months (range: 12– 15 months). During follow-up, continuous improvement of corneal transparency and CDVA was observed in every patient. The only intraoperative complication reported was a peripheric DM microperforations of previous graft–host junction in two eyes. No signs of double anterior chamber, endothelial failure, GF, glaucoma, or other side effects were reported.Conclusion: Our results suggest that modified DALK in patients with GF after PK, preserving a healthy endothelium, is surgically feasible. However, further studies are needed to compare this procedure to PK and other DALK technique variations.Keywords: corneal transplantation, lamellar keratoplasty, graft failure, corneal diseases